Facile synthesis of bio-based reactive flame retardant from vanillin and guaiacol for epoxy resin. (1st June 2020) - Liu, Jingkai; Dai, Jinyue; Wang, Shuaipeng; Peng, Yunyan; Cao, Lijun; Liu, Xiaoqing
Abstract: With the purpose to obtain an eco-friendly flame retardant for epoxy resin, a facile method for the synthesis of a bio-based epoxy monomer containing DOPO units (DGEBDB) from lignin-derived vanillin and guaiacol, was presented in this work. During the synthesis process, guaiacol acted as both reactant and solvent. And it could be recycled in situ and re-used as the fresh one. In order to evaluate the flame retardancy of DGEBDB, it was mixed with diglycidyl ether of bisphenol A (DGEBA) and cured with 4, 4-diaminodiphenylmethane (DDM). Results showed that, DGEBDB demonstrated a good compatibility with DGEBA, and the mechanical properties of cured resins were obviously improved with the addition of DGEBDB. As expected, the limiting oxygen index (LOI) of cured resin reached 30.2% with the content of phosphorus only 0.67 wt%, in which the weight ratio between DGEBDB and DGEBA was 1:9 (B1D9/DDM). When the weight ratio of DGEBDB to DGEBA was further increased to 2:8 for the B2D8/DDM system, the UL-94 V-0 grade was achieved. Meanwhile, the mechanism of DGEBDB in improving the flame retardancy of cured resin was discussed and revealed. This easily available and eco-friendly DGEBDB was proved to be a highly efficient reactive flame retardant for epoxy resin. Highlights: A high-efficient flame retardant for epoxy was synthesized from the renewable resource. Guaiacol acted as both reactant and solvent, it could be recycled and re-used. The flame retardant showed very good compatibility with DGEBA. UL-94 V0 grade epoxy was achieved with the phosphorus content was only 1.27%.